Dublin people - Binchy, Maeve (1940-2012); Bassett, Jennifer (Oxford : Oxford University Press, 1994)
A young country girl comes to live and work in Dublin. Jo is determined to be modern and independent, and to have a wonderful time. But life in a big city is full of strange surprises for a shy country girl ...Gerry Moore is a man with a problem - alcohol. He knows he must give it up, and his family and friends watch nervously as he battles against it. But drink is a hard enemy to fight ...These stories by the Irish writer Maeve Binchy are full of affectionate humour and wit, and sometimes a little sadness.
Lecturas adaptadas en inglés.
ESO34 BAC
Keywords: Lengua inglesa -- Lecturas